2017
DOI: 10.1016/j.engstruct.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Flutter characteristics of twin-box girder bridges with vertical central stabilizers

Abstract: It has been well known that Vertical Central Stabilizers (VCS) have the potential of improving flutter performance of long-span bridges. However, the fundamental flutter mechanisms of VCS are still not fully understood so far. In this study, a series of windtunnel tests involving the combination of six representative heights and four types of VCS were conducted to fundamentally investigate the influence of VCS on flutter performance of twin-box girders with various Slot Width Ratios (SWRs). Experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…These results were extracted from 226 groups of acceleration series recorded at wind speeds lower than 0.5 m/s. By contrast, Table 2 also gave the FEM results calculated by Yang et al (2017) as well as with the identified results by forced vibrations tests conducted by Tan (2012).…”
Section: Modal Parameters and Their Dependence On The Wind Speed 41 I...mentioning
confidence: 99%
“…These results were extracted from 226 groups of acceleration series recorded at wind speeds lower than 0.5 m/s. By contrast, Table 2 also gave the FEM results calculated by Yang et al (2017) as well as with the identified results by forced vibrations tests conducted by Tan (2012).…”
Section: Modal Parameters and Their Dependence On The Wind Speed 41 I...mentioning
confidence: 99%
“…Based on the coupling effect of aerodynamic forces, Yang et al [4][5][6] established the relationship between torsional, vertical, and lateral vibration parameters and flutter derivatives (e.g., using the two-dimensional three-degree-of-freedom coupled flutter analysis method) and studied the flutter mechanism of two typical bridge sections: the closed box girder and two-isolated-girder sections. e flutter of these two sections is caused by negative aerodynamic damping, and the negative aerodynamic damping of the streamlined section is the result of the coupling effect of torsion and vertical motion.…”
Section: Introductionmentioning
confidence: 99%
“…For long-span bridges, the bridge deck is a relatively slender structure with a low structural damping, remarkably low rigidity, high sensitivity to wind load, and high likelihood of wind-induced flutter or galloping (Hu et al, 2015). When the wind forces against the main span gain speed gradually, the bridge deck vibration can be converted from an initial damped vibration to vibration divergence (Hu et al, 2016; Ubertini et al, 2017; Yang et al, 2017), and eventually causing structural collapse. Therefore, during the bridge design phase, accurate and effective prediction of critical flutter wind speed is imperative.…”
Section: Introductionmentioning
confidence: 99%